Oronasal Fistula Closure and Defect Reconstruction: Two Case Reports Using Periodontal Plastic Surgery Principles - Gerardo Chacon; Abdusalam Alrmali; Obada Mandil; Héctor Rodriguez; José Rodriguez; Anas Al‐misurati; Hom‐Lay Wang (Wiley, 2024)
ABSTRACT Objectives Oronasal fistulas are common sequelae following cleft lip and palate surgery and can significantly impact a patient's quality of life. They result from various factors, including surgical techniques, tissue management, and patient‐specific factors. This case report explores the modern approach to oronasal fistula closure using periodontal plastic surgery principles. Materials and Methods The report presents two cases of patients with oronasal fistulas due to previous maxillofacial surgical intervention. These patients underwent microsurgical procedures that involved partial flap thickness preparation of the fistula areas, the use of connective tissue grafts from the palate, and meticulous suturing techniques to ensure graft integrity. The procedures were performed in stages, and postoperative care was provided. Results Both cases demonstrated successful fistula closure and graft survival. The patients reported improvements in breathing, speech, aesthetics, and quality of life. The second case also included guided bone regeneration and implant placement. Conclusions Oronasal fistulas resulting from maxillofacial surgery can be effectively treated using periodontal plastic surgery techniques, significantly improving patients' quality of life and aesthetic outcomes. This approach represents a valuable addition to the existing repertoire of oronasal fistula closure methods.